Reproductive performance of West African dwarf goats in southwestern Nigeria - Adeoye, S.A.O. (International Livestock Centre for Africa, 1985)
A study of the reproductive performance of West African Dwarf goats was undertaken at Fashola (7°31'N, 4°00'E) in southwestern Nigeria from 1982 to 1984. Kidding interval was 261 ± 75 days and litter size 1.6 ± 0.5. Annual reproductive rate was 2.3 kids per doe. Age of dam, month and year of parturition had significant (P<0.05) effects on the kidding interval as did the location in the control group. Neither of two treatments (against PPR and mange and against mange alone) had any significant effect on the kidding interval. Age of dam and treatment both affected the litter size significantly (P<0.05). The data are compared with some other results obtained in Africa.